Analisis Komunikasi Internal dan Kinerja Karyawan di UMKM Mirukiway Bandung - Donni Junipriansa; Nabil Ar Araaf; Savira Najwa (Jurnal Manajemen dan Bisnis Kreatif)
This study aims to examine internal communication and its impact on employee performance at UMKM Mirukiway Bandung. The research employs a qualitative approach with a case study method, collecting data through in-depth interviews and analyzing them using thematic analysis. The findings indicate that open and informal communication patterns support work coordination, enhance task clarity, and motivate employees. However, challenges such as perception differences and operational workload often lead to miscommunication. Efforts to improve communication through training, regular evaluations, and the adoption of technology have been implemented to optimize performance.